Effect of communicating community immunity on COVID-19 vaccine-hesitant people from ethnically diverse backgrounds: an experimental vignette study in the UK. Issue 11 (3rd November 2022) - Stoffel, Sandro T; Kaushal, Aradhna; Grimani, Aikaterini; von Wagner, Christian; Sniehotta, Falko F; Vlaev, Ivo
Abstract : Objectives: Achieving high vaccination coverage is vital to the efforts of curbing the impact of the COVID-19 pandemic on public health and society. This study tested whether communicating the social benefit through community protection for friends and family members versus overall society, affects vaccination intention and perception among a sample enriched with respondents from black and ethnic minority backgrounds. Design: A web-based experimental survey was conducted. Eligible participants were individually randomised, with equal probability, to one of the three experimental vignettes. Setting: England. Participants: We recruited 512 (212 white, 300 ethnically diverse) vaccine-hesitant members from an online panel. Primary and secondary outcome measures: The primary outcome was the intention to get vaccinated against COVID-19. The secondary outcome consisted of a behavioural measure in the form of active interest in reading more about the COVID-19 vaccine. Additional measures included the perceived importance and expected uptake in others, as well as the attitudes towards vaccination. Results: Logistic regression models did not show an effect of the messages on intentions for the overall sample ( society : adjusted OR (aOR): 128, 95% CI 0.88 to 1.88 and friends and family : aOR 1.32, 95% CI 0.89 to 1.94). The role of vaccination in achieving community immunity yielded higher vaccination intentions among study participants with white ethnic background ( society : aOR: 1.94, 95% CI 1.07 to 3.51 and friends and family : aOR 2.07, 95% CI 1.08 to 3.96), but not among respondents from ethnically diverse backgrounds ( society : aOR: 0.95, 95% CI 0.58 to 1.58 and friends and family : aOR 1.06, 95% CI 0.64 to 1.73). The messages, however, did not affect the perceived importance of the vaccine, expected vaccination uptake and active interest in reading more about the vaccine. Conclusions: Thus, although highlighting the social benefits of COVID-19 vaccinations can increase intentions among vaccine non-intenders, they are unlikely to address barriers among ethnically diverse communities.